THE UNSEEN HAND AND THE BALANCE SHEET: TRACING THE SHADOW OF CORRUPTION AND MONEY LAUNDERING ON SRI LANKAN BANK STABILITY AND PROFITABILITY - Wickramarathne , Ishara Nuwan; Muthunayake , Himal; Sandakelum , Isuru (Indian Journal of Finance and Banking, 2025)
The resilience of the financial system depends on the stability and profitability of the banking industry, particularly in developing countries, where financial crimes and poor governance persist as ongoing problems. Concern about money laundering and corruption has grown in Sri Lanka, particularly during periods of stress in the banking industry. However, empirical data on how these illicit activities affect bank-level performance remains limited. This Study examines the stability and profitability of regulated commercial banks in relation to corruption and money laundering. Panel data from 24 licensed commercial banks from 2016 to 2024 are used. To identify institution-specific impacts over time, fixed effects regression models are used to analyse bank profitability and stability metrics, while accounting for bank size and management effectiveness. The empirical findings indicate corruption has a statistically significant negative impact on stability and profitability, and coefficient estimates show that bank performance consistently declines as corruption increases. Money laundering, on the other hand, shows a mixed relationship, with some model specifications indicating a positive, statistically significant association with stability and profitability. While managerial effectiveness is positively correlated with bank stability, bank size hurts profitability but makes a favourable, considerable contribution to stability. The Study’s quantitative results show that while the effects of money laundering are context-dependent and vary across performance characteristics, corruption consistently impairs banks’ financial performance and stability. Overall, the results confirm the asymmetric influence of economic crimes, including money laundering and corruption, on Sri Lankan bank stability and economic performance. JEL Classification Codes: G21, G28, K42, E44.